Limiting Case of the Spin Hypersurface Dirac Operator arising in the positive mass theorem for black holes - Eker, Serhan (Applied mathematics and nonlinear sciences, 2021)
In this paper, we give an explicit form of the scalar curvaure for the limiting case of the eigenvalue of the hypersurface Dirac operator which arises in the positive mass theorem for black holes. Then, we show that the hypersurface is an Einstein.